2018
DOI: 10.3389/fimmu.2018.00259
|View full text |Cite
|
Sign up to set email alerts
|

Immunization Strategies Producing a Humoral IgG Immune Response against Devil Facial Tumor Disease in the Majority of Tasmanian Devils Destined for Wild Release

Abstract: Devil facial tumor disease (DFTD) is renowned for its successful evasion of the host immune system. Down regulation of the major histocompatabilty complex class I molecule (MHC-I) on the DFTD cells is a primary mechanism of immune escape. Immunization trials on captive Tasmanian devils have previously demonstrated that an immune response against DFTD can be induced, and that immune-mediated tumor regression can occur. However, these trials were limited by their small sample sizes. Here, we describe the results… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
45
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
2
2

Relationship

2
6

Authors

Journals

citations
Cited by 35 publications
(45 citation statements)
references
References 33 publications
(43 reference statements)
0
45
0
Order By: Relevance
“…Previous DFT vaccine efforts have used killed DFT cells with adjuvants 62, 63 . A similar approach to treat gliomas in dogs reported that tumor-lysate with CD200 peptides nearly doubled progression-free survival compared to tumor lysate alone 64 .…”
Section: Discussionmentioning
confidence: 99%
“…Previous DFT vaccine efforts have used killed DFT cells with adjuvants 62, 63 . A similar approach to treat gliomas in dogs reported that tumor-lysate with CD200 peptides nearly doubled progression-free survival compared to tumor lysate alone 64 .…”
Section: Discussionmentioning
confidence: 99%
“…Experimentally treating devils with radiation-killed DFTD cells can produce a detectable immune response, which in some cases led to tumor regression in captive animals (Tovar et al 2017). Pye et al (2018) found that devils treated with DFTD cells manipulated to produce MHC class I antigens induce an antibody response in devils released into the wild. Yet despite this progress, it is not yet known whether immunization may be protective against DFTD infection in the field.…”
Section: Current Conservation Strategies For Tasmanian Devilsmentioning
confidence: 99%
“…MHC-I down-regulation in these tumours is due to epigenetic mechanisms and can be reversed by treatment with the pro-inflammatory cytokine interferon gamma (IFNg) (18). However, rare instances of spontaneous DFT1 tumour regression have been described and vaccination and immunotherapy of devils with live MHC-I positive DFT1 cells demonstrate that devils can mount an effective immune response against the disease in some instances (19)(20)(21). We have 5 recently shown that in contrast to DFT1, DFT2 cells express MHC-I molecules, but the expressed alleles are similar between hosts and tumours in the samples analysed (1).…”
Section: Introductionmentioning
confidence: 99%
“…A unique opportunity exists to limit the spread of this 'new' tumour, before it causes the level of infection of DFT1. MHC + -DFT1 cells have become the focus of intense research to determine if they are allogenic to host devils and have potential as a whole cell vaccine against DFT1 (19,21). Preliminary results have shown that MHC + -DFT1 cells can stimulate a protective immune response in host devils but the mechanisms are not understood and the results are variable among host devils.…”
mentioning
confidence: 99%